"Acoustic Space" – Marshall McLuhan Defended Against Himself. (2nd January 2016) - Erlmann, Veit
Abstract: After a spectacular rise over two decades Sound Studies appears to be at a crossroads. Many of its taken-for-granted epistemological assumptions regarding the givenness of a particular domain such as "hearing" or "sound" have become debatable. Marshall McLuhan's largely forgotten concept of "acoustic space" and its complex relationship with the unconscious offers an opportunity to explore alternatives to sensed, emplaced sound as the normative epistemological space of sound studies.